Psoriasis and Atherosclerosis: Is There a Need For Novel Biomarkers Assessing Cardiovascular Risk? - SÜNBÜL, MURAT (BENTHAM SCIENCE PUBL LTD, 2014)
Epidemiological studies indicate increased mortality rates in cohorts of patients with psoriatic arthritis (PsA). Psoriasis is associated with an enhanced cardiovascular risk. The excess mortality in psoriasis and PsA is predominantly due to coronary artery disease. The aim of this review is to overview the biomarkers and/or mediators of increased cardiovascular risk in patients with psoriasis and PsA. We searched through Medline/PubMed to retrieve sources on cardiovascular disease (CVD), related risk factors and inflammatory markers in psoriasis and PsA. We analyzed the relationship between psoriasis and novel vascular biomarkers with potential use for preventive studies. Studies underline the importance of considering psoriatic patients as a high-risk population in terms of CVD. Novel biomarkers of inflammation, thrombosis, oxidative stress and atherosclerosis can provide risk stratification and strategies for early detection and treatment of CVD in patients with psoriasis. A better understanding of the association between psoriasis and vascular risk can help the clinician to manage the increased morbidity and mortality related to CVD.
Keywords: Cardiovascular risk; psoriasis; psoriatic arthritis; inflammation; biomarker; atherosclerosis; PLASMINOGEN-ACTIVATOR INHIBITOR-1; NECROSIS-FACTOR-ALPHA; CORONARY-ARTERY-DISEASE; RHEUMATOID-ARTHRITIS; MYOCARDIAL-INFARCTION; METABOLIC SYNDROME; SUBCLINICAL ATHEROSCLEROSIS; HIGH PREVALENCE; DOUBLE-BLIND; MORTALITY